Insurance and the Nigerian economy - Osoka, Ogala (Lagos, Nigeria Panache Publications, 1992)
The book represents an overview of topical issues in insurance in Nigeria
Includes bibliographical references.
opc 9/8/16
Loans
Keywords: Insurance; Economic policy; Nigeria